A method for quickly verifying the rust-inhibiting effect of rust inhibitors in reinforced concrete

By performing vacuum treatment and electromagnetic field acceleration of chloride ion movement in the acceleration reaction instrument, combined with ultrasonic treatment, the corrosion process of steel bars is rapidly accelerated, and the problem of low verification efficiency of rust inhibitors in the existing technology is solved, and a fast and accurate rust inhibitor is achieved. Performance evaluation.

CN115128215BActive Publication Date: 2025-02-14武汉三源特种建材有限责任公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210728078.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-24
Publication Date
2025-02-14
Estimated Expiration
2042-06-24

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and accurately verify the rust resistance effect of rust resistors in reinforced concrete, resulting in low screening efficiency of rust resistors.

Method used

Accelerated reaction instruments are used to accelerate the movement of chloride ions and electromagnetic fields, combined with ultrasonic treatment, to quickly accelerate the corrosion process of steel bars and shorten the test cycle.

Benefits of technology

The test time for rust resistor verification is significantly shortened, the test efficiency is improved, the test results are regular and stable, and the performance of rust resistor can be quickly and accurately evaluated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115128215B_ABST
    Figure CN115128215B_ABST
Patent Text Reader

Abstract

The present invention provides a method for quickly verifying the rust-proofing effect of a rust inhibitor in reinforced concrete, comprising the following steps: first, placing a concrete sample under vacuum conditions for a certain period of time; second, placing the concrete sample in a composite solution, performing alternating power-on and power-off operations on the composite solution, and performing ultrasonic treatment on the composite solution during the power-off period; third, drying the treated concrete sample and cooling it to room temperature; finally, repeating the above operations for multiple times until the specified number of cycles is completed or the steel bar corrosion area rate in the concrete sample reaches a target value, terminating the test, and calculating the rust-proofing rate of the rust inhibitor. This method directly applies the rust inhibitor to the reinforced concrete environment, and can more intuitively verify the advantages and disadvantages of the effect of the rust inhibitor in reinforced concrete. This method has the advantages of short time, high efficiency, and stable test results, and fills the gap in the rapid verification and detection technology of rust inhibitors in reinforced concrete environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of reinforced concrete admixture effect testing, and in particular relates to a method for quickly verifying the rust-inhibiting effect of a rust inhibitor in reinforced concrete. Background Art

[0002] Concrete is still one of the main building materials today because of its rich raw material sources, low price, simple and mature production process. Under normal circumstances, concrete has a protective effect on the steel bars buried in it. This is because the calcium hydroxide produced by cement hydration and the highly alkaline pore fluid of potassium and sodium ions can passivate the surface of the steel bars to form a dense oxide film protective layer. However, due to factors such as concrete carbonization, it is easy to cause the pH to decrease or be corroded and polluted by chlorides, which can easily destroy the stable passivation film and cause steel corrosion. Steel bar corrosion is a spontaneous process, the amount of corrosion increases exponentially, and the economic losses increase exponentially. The continuous accumulation of steel bar corrosion products produces expansion stress, causing concrete cracking and spalling, and the corrosion of steel bars in concrete in complex and harsh engineering environments is very harmful to the durability of the structure. The introduction of rust inhibitors can effectively reduce the corrosion rate of steel bars and inhibit the deterioration of steel bars. It is a more practical and simple method to prevent and slow down the corrosion of chloride ions on concrete. Rust inhibitors have the advantages of long-term effectiveness after one-time use, simple construction, and no change in the properties of concrete itself, and are widely used in reinforced concrete anti-corrosion projects.

[0003] As an admixture to increase the durability of concrete, the effect of rust inhibitor takes a long time to manifest, and it is difficult to judge the quality of its rust inhibition performance in a short time. Nowadays, most of the methods used to verify the performance of rust inhibitors are to simulate the pore solution of concrete and use the potential change to judge its performance. However, as an admixture used in combination with concrete, it is unreasonable to study the rust inhibition performance of admixtures without considering the concrete environment. The test results also have certain deviations from the rust inhibition performance data in the actual concrete environment.

[0004] The percentage test of steel bar corrosion area in concrete under salt water immersion and drying environment in JT / T 537-2018 "Rust Inhibitors for Reinforced Concrete" is to observe the corrosion of steel bars in a concrete environment, which can more accurately reflect the effectiveness of the rust inhibitor. In the test, the specified type of steel bars are placed in 100mm*100mm*46mm concrete for molding, and the mold is removed the next day. The exposed steel bars are molded with mortar to seal the remaining space. After standard curing until the 7th day, the test block is placed in an oven at 80℃ and dried for 24 hours to remove excess moisture and then the cycle test is started. It is soaked in 3.5% NaCl solution for 96 hours and placed in a 60℃ oven for drying for 72 hours to complete a cycle test. The entire test lasts at least 4 cycles to see the effect of the rust inhibitor. The fastest test cycle is as long as 36 days. The longer test cycle directly affects the efficiency of rust inhibitor screening.

[0005] Based on this, providing a method that can more quickly and accurately verify the rust-inhibiting effect of rust inhibitors in reinforced concrete can accelerate the verification of the effect of rust inhibitors on-site in construction projects, which is a technical problem that needs to be solved urgently. Summary of the invention

[0006] The purpose of the present invention is to provide a method for verifying the rust-inhibiting effect of a rust inhibitor in reinforced concrete more quickly and accurately in view of the deficiencies in the prior art.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solution: providing a method for quickly verifying the rust-inhibiting effect of a rust inhibitor in reinforced concrete, comprising the following steps:

[0008] S1. Adding steel bars into concrete, curing and drying to obtain concrete samples, wherein the concrete samples include sample A without rust inhibitor and sample B with rust inhibitor;

[0009] S2. placing the concrete sample in an accelerated reaction apparatus and maintaining it under vacuum conditions for 2 to 4 hours;

[0010] S3, injecting a composite solution of NaCl and MgSO4 with a mass concentration of 5-15% into the accelerated reaction instrument, so that the concrete sample is completely immersed in the composite solution for 2-6 hours; during the immersion process, the composite solution is alternately powered on and off; and during the power-off period, the composite solution is subjected to ultrasonic treatment;

[0011] S4, taking out the concrete sample treated in step S3, drying it, and cooling it to room temperature;

[0012] S5. Repeat steps S2 to S4 for multiple times until the specified number of cycles is completed or the corrosion area ratio of the steel bars in the concrete sample reaches the target value, terminate the test, and calculate the rust inhibition rate of the rust inhibitor.

[0013] In the present invention, in order to effectively shorten the time required for verification, the inventors have improved many key factors affecting the detection process to achieve accelerated corrosion of steel bars:

[0014] First, the concrete sample is vacuum treated using an accelerated reaction instrument to expel the air in the pores inside the concrete sample, making the concrete sample present a negative pressure state, which is conducive to the subsequent adsorption of the solution;

[0015] Secondly, the composite solution is injected into the accelerated reaction instrument to immerse the vacuum-treated concrete specimens, and the composite solution is alternately powered on and off during the immersion process. Under the action of the electric field, on the one hand, the chloride ions in the solution move toward the anode, accelerating the chloride ions to enter the concrete specimen; after the electric field is applied, the system's potential energy is converted into ion kinetic energy and thermal energy, and the thermal motion frequency of the chloride ions in the solution increases, accelerating them to enter the concrete through the capillary pores. On the other hand, the metal steel bars in the concrete specimen also form a weak electric field relative to the surrounding concrete environment under the action of the magnetic field, attracting the free chloride ions inside the concrete to accelerate their movement toward the steel bars. As the chloride ions in the external solution continue to enter, they gradually accumulate on the surface of the steel bars and catalyze the corrosion reaction.

[0016] At the same time, when the cathode is powered, water is electrolyzed to continuously generate oxygen, part of which dissolves in water to increase the oxygen content in the water, and the other part adheres to the surface of the test block or overflows into the air, providing the necessary conditions for the steel bar corrosion reaction. Furthermore, the reaction container forms a magnetic field through the cathode and the anode, and the water molecules in the reaction container are magnetized to reduce the agglomeration of water molecules in the composite solution, so that they can better enter the concrete through adsorption and diffusion, and also provide a basis for the directional movement of chloride ions in the test block in the later stage.

[0017] Thirdly, ultrasonic operation of the composite solution during power outage can redisperse the chloride ions that have directionally moved and concentrated on one side of the reaction vessel, ensuring that the chloride ions in the entire reaction vessel are uniform and stable; in addition, the energy conversion generated by ultrasonic vibration accelerates the movement of chloride ions and promotes the rapid progress of the corrosion process.

[0018] Finally, in the subsequent drying stage, the evaporation of water makes the pores inside the concrete sample transparent, allowing more oxygen to enter the pores, which can effectively accelerate the corrosion process of the steel bars in the concrete in the next round of repeated operations and further improve the test efficiency.

[0019] Furthermore, in step S1, the specific preparation method of the concrete sample includes: firstly, placing the steel bar in the fixing clamp, moving the steel bar and the fixing clamp as a whole into the mold, adding the rust inhibitor and the raw materials into the stirring pot and mixing them with a 3% sodium chloride solution. The fresh concrete is placed in the mold and vibrated to be dense, and the steel bar fixing clamp is taken out after curing for 24 hours, and the exposed steel bar is sealed and cured with rich mortar until the 7th day. The specific operation of the drying is: placing the cured concrete sample in a blast drying oven at 80-120°C, and drying for 20-28 hours to remove the capillaries in the sample and excess moisture on the surface.

[0020] In step S2, a cavity is provided inside the accelerated reaction instrument, and the cavity is used to contain the composite solution and place the concrete sample. The cavity adopts a sealable structure to facilitate vacuum negative pressure operation; the top and bottom of the cavity are respectively fixed with an anode plate and a cathode plate, and an ultrasonic vibration device is arranged around the cavity, and the power supply of the two plates and the ultrasonic device is controlled by a timing switch.

[0021] Preferably, in step S2, the vacuum degree of the vacuum condition is 0.8-1.2 MPa.

[0022] Preferably, in step S3, the mass ratio of NaCl to MgSO4 in the composite solution is 3:2. Compared with conventional treatment solutions (generally using a 3.5wt% NaCl solution), the composite solution used in the present invention has the characteristics of synergistically accelerating destruction. When the steel bar is placed in concrete, MgSO4 is added to the composite solution to accelerate the destruction of the concrete stability, reduce the protective effect of the concrete on the steel bar, increase the penetration depth of NaCl, increase the erosion effect, and quickly reflect the product effect.

[0023] Furthermore, in step S3, the alternating power-on and power-off operations on the composite solution include: contacting and fixing the anode plate with the upper surface of the composite solution, placing the cathode plate at the bottom of the composite solution, connecting alternating current, and forming an electric field at the upper and lower ends of the accelerated reaction instrument.

[0024] Preferably, the materials used to make the bipolar plates are selected from corrosion-resistant inert metals, including but not limited to copper, platinum, etc. In specific operations, the position of the upper anode plate is adjusted according to the liquid level inside the cavity to ensure that it is in contact with the immersion liquid surface.

[0025] Furthermore, the ultrasonic frequency of the ultrasonic treatment is 20000 Hz to 40000 Hz. Ultrasonic waves of this frequency can generate high-frequency amplitudes, which can generate small vacuum bubbles or gaps in the liquid. The application of this mechanical stress can separate the aggregated particles in the solution.

[0026] Preferably, the power-on time is 20 to 50 minutes, and the power-off time is 10 to 40 minutes; the ultrasonic treatment starts after each power-on and ends before the next power-on.

[0027] In some preferred embodiments, the power-on time is 20 minutes, the power-off time is 40 minutes, and then the power-on time is 20 minutes, the power-off time is 40 minutes, and then the power-on time is 20 minutes, the power-off time is 40 minutes, and the alternating power-on and power-off operations last for a total of 4 hours. The ultrasonic device is turned on 20 minutes after the power is turned on to form the electric field, and the working time of the ultrasonic device is set to 40 minutes, and the ultrasonic device continues to work 20 minutes after the ultrasonic device stops working, and the operation and stopping of the ultrasonic device are repeated for a total of 4 hours.

[0028] Furthermore, in step S4, the composite solution remaining on the surface of the taken-out concrete sample is wiped dry, and the concrete sample is dried at 80 to 120° C. for 8 to 14 hours, and then cooled to room temperature.

[0029] Furthermore, in the step S5, in two adjacent repeated operations, the orientation of the concrete sample molding surface along the vertical direction is adjusted. Specifically, in the above-mentioned cyclic operation process, the molding surface can be placed upward when the number of cycles is an odd number, and the molding surface can be placed downward when the number of cycles is an even number. The advantage of this treatment is that each time the chloride ions are cycled, they move from bottom to top under the action of the electrode, and the chloride ion concentration on one side of the specimen facing the cathode is higher than that on the other side. The purpose of reversing the direction is to allow the chloride ions to penetrate evenly on both sides.

[0030] In some preferred implementations, in order to facilitate the test operation, the number of repetitions in step S5 is set to 6 times (ie, a total of 7 cycles are completed). After 7 cycles are completed, concrete sample A is randomly selected to split and calculate the steel bar corrosion area.

[0031] Furthermore, the rust inhibition rate of the rust inhibitor in step S5 refers to the percentage reduction of the corrosion area, which is calculated as follows: percentage reduction of the corrosion area = [(percentage of steel bar corrosion area of ​​sample A - percentage of steel bar corrosion area of ​​sample B) / percentage of steel bar corrosion area of ​​sample A] × 100%.

[0032] Furthermore, the total test time of the method for quickly verifying the rust-inhibiting effect of the rust inhibitor in reinforced concrete is 11 to 16 days, which can save more than 50% of the test time compared with conventional detection methods.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The present invention provides a method for quickly verifying the rust-inhibiting effect of a rust inhibitor in reinforced concrete. The rust inhibitor is directly applied to the reinforced concrete environment without using a concrete environment simulation liquid. This method can more intuitively verify the effectiveness of the rust inhibitor in reinforced concrete.

[0035] (2) The present invention provides a method for quickly verifying the rust-proofing effect of a rust inhibitor in reinforced concrete. The method takes into account many factors that affect steel corrosion, and comprehensively utilizes vacuum, electromagnetic field, and ultrasonic processing methods to directionally accelerate the movement of chloride ions into the concrete sample, significantly accelerating the corrosion rate of the steel bars in the concrete sample, and having a significant effect on quickly verifying the rust-proofing performance of the steel rust inhibitor in concrete. The method can effectively shorten the test time and improve the test efficiency, and the test results are regular and stable, filling the gap in the rapid verification and detection technology of rust inhibitors in reinforced concrete environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 A schematic flow chart of a method for quickly verifying the rust-inhibiting effect of a rust inhibitor in reinforced concrete provided by the present invention. DETAILED DESCRIPTION

[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0039] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited thereto.

[0040] Example 1

[0041] Concrete test block sample A without rust inhibitor and concrete test block sample B with steel bar rust inhibitor were prepared respectively (the rust inhibitor was SY-R type rust inhibitor produced by Wuhan Sanyuan Company, and the added amount accounted for 5% of the total mass of the cementitious material). The specific test method is as follows:

[0042] Concrete test blocks were molded according to the regulations, and the steel bars with rust removed from the surface were placed in the concrete test pieces, and molded and cured until the 7th day; the molded and cured concrete test pieces were taken out of the standard curing room and placed in a 105°C forced air drying oven, and dried for 24 hours to remove excess moisture in the pores of the test pieces; the concrete test pieces were taken out of the forced air drying oven, cooled for 1 hour at room temperature, and then placed in an accelerated reaction instrument (the molded surface was placed upward when the number of cycles was an odd number, and the molded surface was placed downward when the number of cycles was an even number), and the vacuum was sealed and evacuated to maintain a vacuum negative pressure of 1MPa Maintain for 4 hours to remove the air in the gaps of the test block, so that the test block is in a negative pressure state for better adsorption later; after a period of vacuum negative pressure, open the water inlet valve and immediately inject a 5% concentration of composite solution into the reaction instrument until the test block in the cavity is completely submerged, and then maintain this immersion state for 6 hours; when the solution completely immerses the test block, fix the anode plate so that its upper surface is in contact with the soaked solution, and the anode plate on the upper part of the reaction container and the cathode plate at the bottom of the container are connected to alternating current to form an electric field at the upper and lower ends of the reaction container, driving the chloride ions in the solution to move in a directional manner, and set the power supply to stop after 20 minutes, and continue to work after 40 minutes, and repeat this process for 2 hours; 20 minutes after the power is turned on to form the electric field, turn on the ultrasonic device (40000 Hz) and set it to stop after 40 minutes, and continue to work after 20 minutes, and repeat this process for 4 hours; after 4 hours, disconnect all power supplies, collect the solution in the reaction tank, take out the test block and wipe the surface of the specimen. Place the specimen in a 105°C forced air drying oven for 8 hours. After 8 hours, take out the specimen and cool it down indoors for 1 hour to complete one cycle. After 7 cycles, randomly select specimens for splitting to calculate the steel corrosion area.

[0043] Example 2

[0044] Concrete test block sample A without rust inhibitor and concrete test block sample B with steel bar rust inhibitor were prepared respectively (the rust inhibitor was SY-R type rust inhibitor produced by Wuhan Sanyuan Company, and the added amount accounted for 5% of the cementitious material). The specific test method is as follows:

[0045] Concrete test blocks were formed according to the regulations, and the steel bars with rust removed from the surface were placed in the concrete test pieces, and the forming and curing lasted until the 7th day; the formed and cured concrete test pieces were taken out of the standard curing room and placed in a 105°C forced air drying oven, and dried for 24 hours to remove excess moisture in the pores of the test pieces; the concrete test pieces were taken out of the forced air drying oven, cooled at room temperature for 1 hour, and then placed in an accelerated reaction instrument (the forming surface was placed upward when the number of cycles was an odd number, and the forming surface was placed downward when the number of cycles was an even number), and the vacuum was sealed and evacuated, and the vacuum negative pressure was maintained at 1MPa for 3.5 hours to remove the air in the gaps of the test pieces, so that the test pieces were in a negative pressure state, so that they could be replaced later. Good adsorption; after a period of vacuum negative pressure, open the water inlet valve and immediately inject 8% concentration of composite solution into the reaction instrument until the test block in the cavity is completely submerged, and then maintain this immersion state for 4 hours; when the solution completely immerses the test block, fix the anode plate so that its upper surface contacts the soaked solution, and connect the anode plate on the upper part of the reaction container and the cathode plate at the bottom of the container with alternating current to form an electric field at the upper and lower ends of the reaction container, driving the chloride ions in the solution to move in a directional manner, and set the power supply to stop after 30 minutes, and continue to work after 30 minutes, and repeat this process for 4 hours; turn on the ultrasonic device (40000Hz) 30 minutes after the power is turned on to form the electric field, and set it to stop after 30 minutes, and continue to work after 30 minutes, and repeat this process for 4 hours; after 4 hours, disconnect all power supplies, collect the solution in the reaction tank, take out the test block and wipe the surface of the test piece. Place the specimen in a 95°C forced air drying oven for 12 hours; after 12 hours, take out the specimen and cool it down indoors for 1 hour to complete one cycle. After 7 cycles, randomly take the specimens for splitting to calculate the steel corrosion area.

[0046] Example 3

[0047] Concrete test block sample A without rust inhibitor and concrete test block sample B with steel bar rust inhibitor were prepared respectively (the rust inhibitor was SY-R type rust inhibitor produced by Wuhan Sanyuan Company, and the added amount accounted for 5% of the cementitious material). The specific test method is as follows:

[0048] Concrete test blocks were molded according to the regulations, and the steel bars with rust removed from the surface were placed in the concrete test pieces, and molded and cured until the 7th day; the molded and cured concrete test pieces were taken out of the standard curing room and placed in a 100°C forced air drying oven, and dried for 24 hours to remove excess moisture in the pores of the test pieces; the concrete test pieces were taken out of the forced air drying oven, cooled at room temperature for 1 hour, and then placed in an accelerated reaction instrument (the molded surface was placed upward when the number of cycles was an odd number, and the molded surface was placed downward when the number of cycles was an even number), sealed and evacuated, and the vacuum negative pressure was maintained at 1MPa for 2.5 hours, in order to remove the air in the gaps of the test pieces, so that the test pieces were in a negative pressure state, so as to facilitate better adsorption in the later stage; after a period of vacuum negative pressure, the water inlet valve was opened and 12% concentration of Composite solution, until the test block in the cavity is completely submerged, and then maintain this immersion state for 3 hours; when the solution completely immerses the test block, fix the anode plate so that it contacts the upper surface of the soaked solution, connect the anode plate on the upper part of the reaction container to the cathode plate at the bottom of the container with alternating current, form an electric field at the upper and lower ends of the reaction container, drive the chloride ions in the solution to move in a directional manner, and set the power supply to stop after 40 minutes, and continue to work after 20 minutes, repeat this process for 3 hours; turn on the ultrasonic device (40000Hz) 40 minutes after the power supply is turned on to form an electric field and set it to stop after 20 minutes, and continue to work after 40 minutes, repeat this process for 3 hours; after 3 hours, disconnect all power supplies, collect the solution in the reaction pool, take out the test block and wipe the surface of the test piece. Put it in a blast drying oven at 105℃ and keep it for 10 hours; after 10 hours, take out the test piece and cool it indoors for 1 hour. This is to complete a cycle. After 7 cycles, randomly take the test piece for splitting to calculate the steel bar corrosion area.

[0049] Example 4

[0050] Concrete test block sample A without rust inhibitor and concrete test block sample B with steel bar rust inhibitor were prepared respectively (the rust inhibitor was SY-R type rust inhibitor produced by Wuhan Sanyuan Company, and the added amount accounted for 5% of the cementitious material). The specific test method is as follows:

[0051] Concrete test blocks were molded according to the regulations, and the steel bars with rust removed from the surface were placed in the concrete test pieces, and molded and cured until the 7th day; the molded and cured concrete test pieces were taken out of the standard curing room and placed in a 100°C forced air drying oven, and dried for 24 hours to remove excess moisture in the pores of the test pieces; the concrete test pieces were taken out of the forced air drying oven, cooled at room temperature for 1 hour, and then placed in an accelerated reaction instrument (the molded surface was placed upward when the number of cycles was an odd number, and the molded surface was placed downward when the number of cycles was an even number), sealed and evacuated, and the vacuum negative pressure was maintained at 1MPa for 2 hours, in order to remove the air in the gaps of the test pieces, so that the test pieces were in a negative pressure state, so as to facilitate better adsorption in the later stage; after a period of vacuum negative pressure, the water inlet valve was opened and 15% concentration of complex was immediately injected into the reaction instrument Combine solution until the test block in the cavity is completely submerged, and then maintain this immersion state for 2 hours; when the solution completely immerses the test block, fix the anode plate so that it contacts the upper surface of the soaked solution, connect the anode plate on the upper part of the reaction container to the cathode plate at the bottom of the container with alternating current, form an electric field at the upper and lower ends of the reaction container, drive the chloride ions in the solution to move in a directional manner, and set the power supply to stop after 50 minutes, and continue to work after 10 minutes, repeat this process for 2 hours; turn on the ultrasonic device (40000Hz) 50 minutes after the power is turned on to form the electric field and set it to stop after 10 minutes, and continue to work after 50 minutes, repeat this process for 4 hours; after 4 hours, disconnect all power supplies, collect the solution in the reaction pool, take out the test block and wipe the surface of the test piece. Put it in a blast drying oven at 120℃ and keep it for 8 hours; after 8 hours, take out the test piece and cool it indoors for 1 hour. This is to complete a cycle. After 7 cycles, randomly take the test piece for splitting to calculate the steel bar corrosion area.

[0052] Comparative Example

[0053] Concrete test block sample A without rust inhibitor and concrete test block sample B with steel bar rust inhibitor were prepared respectively (the rust inhibitor was SY-R type rust inhibitor produced by Wuhan Sanyuan Company, and the added amount accounted for 5% of the cementitious material), and the rust inhibition effect of the above samples was verified using the method of JT / T 537-2018 "Rust Inhibitor for Reinforced Concrete".

[0054] The specific operation is as follows: Place the polished and rust-free 120mm steel bar in the fixing clamp, fix 10mm on each end, and ensure that the 100mm length of the steel bar is in contact with the concrete. Move the steel bar and the fixing clamp as a whole into the mold, and mix the sample A concrete in a mixing pot with a 3% concentration of sodium chloride solution according to the established mix ratio; when mixing the sample B concrete, add the rust inhibitor and raw materials into the mixing pot and mix with a 3% concentration of sodium chloride solution. The mixed concrete of Samples A and B was put into the mold and vibrated to make it dense. After curing for 24 hours, the steel bar fixing clamps were taken out, and the exposed steel bars were sealed with rich-proportion mortar and cured until the 4th day. After demolding, they were cured until the 7th day. The test pieces were placed in an oven at 80°C for 24 hours to remove excess moisture and then the cycle test was started. They were immersed in 3.5% NaCl solution for 96 hours, taken out and dried in an oven at 60°C for 72 hours to complete a cycle test. After four cycles, one group of samples A were split to calculate the steel bar corrosion area. When the corrosion area rate of sample A was less than 15%, the cycle operation was continued until the steel bar corrosion area was not less than 15% and the test was terminated.

[0055] Test data

[0056] The percentage of steel bar corrosion area of ​​samples A and B in Examples 1-4 and the comparative example was calculated, and the rust inhibition rate of the rust inhibitor (i.e., the percentage of reduction in the corrosion area) was calculated based on the above data. The total test time of Examples 1-4 and the comparative example was counted respectively. The relevant data are shown in Table 1 below:

[0057] Table 1

[0058]

[0059] As can be seen from the above table,

[0060] By using the method for quickly verifying the rust inhibition effect of the rust inhibitor in reinforced concrete provided by the present invention, the rust inhibition rate (corrosion area reduction percentage) data obtained is basically consistent with the results of the comparative example tested by the standard method, and the maximum error is within 1.6%. At the same time, the total test time of Examples 1-4 of the present invention is controlled within 16 days, which can save up to 72% of the test time compared with the comparative example.

[0061] This fully demonstrates that the method provided by the present invention for quickly verifying the rust-inhibiting effect of rust inhibitors in reinforced concrete can significantly accelerate the corrosion rate of steel bars in concrete specimens, has the advantages of short test time, high efficiency, and stable test results, and has a significant effect on quickly verifying the rust-inhibiting performance of steel bar rust inhibitors in concrete.

[0062] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of the specification of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for quickly verifying the rust-inhibiting effect of a rust inhibitor in reinforced concrete, comprising the following steps: S1. Adding steel bars into concrete, curing and drying to obtain concrete samples, wherein the concrete samples include sample A without rust inhibitor and sample B with rust inhibitor; S2. placing the concrete sample in an accelerated reaction apparatus and maintaining it under vacuum conditions for 2 to 4 hours; S3, injecting a composite solution of NaCl and MgSO4 with a mass concentration of 5% to 15% into the accelerated reaction instrument, so that the concrete sample is completely immersed in the composite solution for 2 to 6 hours; during the immersion process, the composite solution is alternately powered on and off; and during the power-off period, the composite solution is subjected to ultrasonic treatment; S4, taking out the concrete sample treated in step S3, drying it and cooling it to room temperature; S5, repeating steps S2 to S4 for multiple times until the specified number of cycles is completed or the corrosion area rate of the steel bars in the concrete sample reaches the target value, terminating the test and calculating the rust inhibition rate of the rust inhibitor; In step S3, the composite solution is alternately powered on and off, including: the anode sheet is contacted with and fixed to the upper surface of the composite solution, the cathode sheet is arranged at the bottom of the composite solution, an alternating current is connected, an electric field is formed at the upper and lower ends of the accelerated reaction instrument, and the power is alternately turned on and off; The power-on time is 20 to 50 minutes, and the power-off time is 10 to 40 minutes; the ultrasonic treatment starts after each power-on and ends before the next power-on; the ultrasonic frequency of the ultrasonic treatment is 20,000 Hz to 40,000 Hz.

2. The method according to claim 1, characterized in that In step S1, the curing time is 7 days, the drying temperature is 80-120° C., and the drying time is 20-28 hours.

3. The method according to claim 1, characterized in that In step S2, the vacuum degree of the vacuum condition is 0.8-1.2 MPa.

4. The method according to claim 1, characterized in that: In step S3, the mass ratio of NaCl to MgSO4 in the composite solution is 3:

2.

5. The method according to claim 1, characterized in that In step S4, the composite solution remaining on the surface of the taken-out concrete sample is wiped dry, and the concrete sample is dried at 80-120° C. for 8-14 hours, and then cooled to room temperature.

6. The method according to claim 1, characterized in that In step S5, in two adjacent repeated operations, the orientation of the concrete sample molding surface along the vertical direction is adjusted.

7. The method according to claim 1, characterized in that The total test time of the method for quickly verifying the rust-inhibiting effect of the rust inhibitor in reinforced concrete is 11 to 16 days.

Citation Information

Patent Citations

  • Reinforced concrete corrosion test device and test method

    CN105547988A

  • Reinforced concrete sample and preparation method and application thereof

    CN111795880A